Research and Design of Nuclear Fuel Manipulate Crane ControlSystem - Zhaohui Mu; Rao Liu; Weidong Li (Institute of Advanced Engineering and Science, 2014)
In order to solve the disadvantages of the Nuclear Fuel Manipulate Crane (ab. MC), the control system of MC is researched and designed, which is based on the operation experiences about Nuclear Fuel Transtion and Storage System (ab.PMC) in Daya Bay and Ling’ao Nuclear Power Plant.The new control system adopts single failure principle and makes use of the Device-net technology that is diffusely applied and extraordinary tried in practice. There are two Device-nets and one Ethernet, the two kinds of nets are combined.Applying the new technologies and new equipments, the new control system solves the defects which Ethernet and a single set of PLC don’t satisfy single failure principle, improves the safety and whole performance of MC loading and unloading of nuclear fuel assembly, and makes control system simply to wire. According to the design of the new control system, the product of MC has been successfully applied to Educate Center in Daya Bay Nuclear Power Site and FangchenggangNuclear Power Plant, and the result is obvious. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4835